ANALISA PERUBAHAN TEGANGAN TERHADAP INTENSITAS CAHAYA PADA LAMPU CFL DAN LAMPU LED - Andri Andri; Yulisman Yulisman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Electrical energy is a necessity from time to time and energy has an important role for technological development. Technology that continues to develop is the development of lamps for lighting many different types of lamps. In this study, two different types of lamps were tested, namely flourecent lamps of the CFL type (compact flourecent lamp) and LED lamps (light emitting diode) which aims to determine the effect of changes in voltage on the intensity of the light produced. Change the voltage using a slide AC voltage regulator with a voltage rage from 60 volt to 220 volt. The method used is the zonal cavity method where the room to be used is divided into three areas, namely the ceiling area, the space are, and the floor area. The CFL lamp used is a 20 watt spiral lamp witch has a lumen of 1300lm and a 20 watt LED lamp which has a lumen of 2000 lm. These lamps are a necessity so that research on the analysis of voltage changes on light intensity in CFL lamps and LED lamps can be achieved. Keywords: light intensity, CFL lamps, LED lamps, Space area method, Slide regulator